The Impact of Whole-Body Electromyostimulation on Body Posture and Trunk Muscle Strength in Untrained Persons - Ludwig, Oliver; Berger, Joshua; Becker, Stephan; Kemmler, Wolfgang; Fröhlich, Michael (Frontiers in Physiology, 2019)
Muscular imbalances of the trunk muscles are held responsible for changes in body posture. At the same time, whole-body electromyostimulation (WB-EMS) has been established as a new training method that enables simultaneous activation of many muscle groups. This study was aiming to analyze if a 10-week WB-EMS training changes posture-relevant parameters and/or improves isometric strength of the trunk extensors and flexors, and if there are differences based on stimulation at 20 Hertz and 85 Hertz. A total of 58 untrained adult test persons were randomized into three groups, a control group (CON), and two training groups with 20 Hz stimulation frequency (TR20) and with 85 Hz respectively (TR85). Anthropometric parameters, trunk extension and flexion forces, and posture parameters were determined before and after a 10-week WB-EMS training program (15 applications, 9 exercises). Differences between the groups were calculated for pre- and post-tests using univariate ANOVA and between the test times using repeated (2x3) ANOVA. Comparisons of pairs were calculated post-hoc based on Fisher (LSD). No differences between the groups were found for the posture parameters. The post-hoc analysis of both trunk flexion and trunk extension values showed a significant difference between the groups TR85 and CON but no difference between the other group pairs. A 10-week whole-body electrostimulation training with a stimulation frequency of 85 Hz in contrast to training with a stimulation frequency of 20 Hz improves the core muscle strength of an untrained group but both training regimes do not significantly change posture parameters.